Utilization of Diagnostic Imaging and Ionization Radiation Exposure Among an Inflammatory Bowel Disease Inception Cohort. Issue 6 (27th September 2019) - Nguyen, Geoffrey C; Low, Daniel; Chong, Rachel Y; Diong, Christina; Chawla, Tanya
Abstract : Inflammatory bowel disease frequently requires abdominal imaging, which often exposes patients to ionizing radiation. Crohn's disease patients on average have higher cumulative ionizing radiation exposure than ulcerative colitis patients. The utilization of abdominal computed tomography seems to be declining, whereas the use of magnetic resonance imaging is rising. Abstract: Background: Abdominal imaging is important in managing inflammatory bowel disease (IBD). We characterized utilization of imaging and exposure to ionizing radiation. Methods: We enumerated abdominal diagnostic imaging in a population-based cohort of IBD patients between 1994 and 2016. Trends in utilization of abdominal computed tomography (CT), magnetic resonance imaging (MRI), and ultrasound were characterized. Cumulative doses of ionizing radiation were compared between IBD patients and non-IBD controls and between Crohn's disease (CD) and ulcerative colitis (UC) patients. Regression models were constructed to assess predictors of high ionizing radiation exposure. Results: There were 72, 933 incident cases of IBD. During the first 5 years of diagnosis, IBD patients were exposed to nearly 6-fold higher exposure to cumulative ionizing radiation attributable to abdominal imaging compared with non-IBD controls (18.6 mSv vs 2.9 mSv). Cumulative ionizing radiation exposure was higher in CD than UC (26.0 mSv vs 12.0 mSv; P < 0.001). Crohn's disease patients were more than twice as likely as UC patients to exceed 50 mSv (15.6% vs 6.2%; P < 0.001) and 100 mSV (5.0% vs 2.1%; P < 0.001). There was geographic variation in ionizing radiation exposure, and individuals of lower income were more likely to have high exposure. Utilization of abdominal MRI has increased substantially, peaking between 2007 and 2012 and increasing annually at 34%, which coincided with an annual 2% decline in the use of abdominal CT. Conclusions: Crohn's disease patients are at highest risk for high exposure to ionizing radiation, with a subgroup receiving potentially harmful levels. Increasing utilization and access to abdominal MRI may alleviate exposure.